Especially vulnerable victims of sexual abuse: obtaining testimony - Vara, Alba (2021)
In sexual crimes, the special characteristics of some people make them potentially vulnerable victims. Faced with the responsibility and legislative obligation to act immediately in defense of their rights and guarantee their protection, the professionals of the police and judicial context who intervene in obtaining the testimony have the challenge to adapt the procedures for obtaining and evaluating their testimonies. Previous investigations confirm misinformation and consequent police and judicial malpractice in cases of sexual abuse of especially vulnerable victims: high delay in complaints, repeated interrogations and use of inappropriate questions. This article analyzes all these influencing factors and gives some recommendations to improve the procedures for obtaining their testimonies. Finally, it warns about the possible suggestion that could derive from the misuse of procedures that seek to improve the amount of information recovered, but that can contribute to generating false memories.